Benefits of Using an Appropriately Formulated Wipe to Clean Diapered Skin of Preterm Infants. (February 2019) - Vongsa, Rebecca; Rodriguez, Karien; Koenig, David; Cunningham, Corey
The skin of premature infants is underdeveloped rendering it more prone to break down and irritation. Therefore, special care is needed to protect premature skin and ensure it is not adversely affected. Many health care professionals advise using just water and cloth to clean diapered skin after a bowel movement despite evidence that shows improved infant skin health with the use of modern appropriately formulated baby wipes. This article describes the unique physiology of premature infant skin, reviews clinical evidence comparing use of baby wipes to water and cloth, and describes attributes of appropriately formulated baby wipes.